Does the foreign interest rate matter for monetary policy? Evidence from nonlinear Taylor rules - Ansgar Belke; Joscha Beckmann; Christian Dreger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Abstract. Deviations of policy interest rates from the levels implied by the Taylor rule have been persistent after the turn of the century even before the financial crisis. These deviations could be due to lower real interest rates, as stated by the savings glut hypothesis as well as the apparent success of monetary policy in combating inflation. Alternatively, they might reflect the omission of relevant variables in the standard rule, such as international dependencies in the interest rate setting of central banks. By using a smooth transition regression approach for three major central banks, this paper provides evidence for nonlinear threshold dynamics. In fact, the foreign interest rate is well-suited to improve standard Taylor-Rules.
Keywords: E43; E52; E42; 330